2016
DOI: 10.1016/s1553-7250(16)30107-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Hospitalwide Implementation of a Standardized Discharge Summary in an Electronic Health Record

Abstract: Background The hospital discharge summary is the primary method used to communicate a patient's plan of care to the next provider(s). Despite the existence of regulations and guidelines outlining the optimal content for the discharge summary and its importance in facilitating an effective transition to post-hospital care, incomplete discharge summaries remain a common problem that may contribute to poor post-hospital outcomes. Electronic health records (EHRs) are regularly used as a platform upon which standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…A few US organizations have developed templates, outlines, or checklists to standardize their own DSs [ 33 - 35 ], but each of them organizes patient information differently. Moreover, even though a 2009 Transitions of Care Consensus Conference produced a list of items that participants recommended be included in transition records [ 17 ], recent research indicates that EHR-generated discharge summaries in the United States continue to omit data that outpatient providers need to effectively coordinate care [ 27 , 36 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few US organizations have developed templates, outlines, or checklists to standardize their own DSs [ 33 - 35 ], but each of them organizes patient information differently. Moreover, even though a 2009 Transitions of Care Consensus Conference produced a list of items that participants recommended be included in transition records [ 17 ], recent research indicates that EHR-generated discharge summaries in the United States continue to omit data that outpatient providers need to effectively coordinate care [ 27 , 36 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other principles useful in the implementation of an eDS are being considered, including the juxtaposition of allowing flexibility while ensuring key criteria are included. 40 If found to improve the quality of eDS, these enhancements could be implemented within eDS across EMRs within Australia.…”
Section: Future Directionmentioning
confidence: 99%
“…14 Studies to date have demonstrated that the after-visit summary is valued by both patients and primary care physicians. 15 The EHR is now increasingly used to generate discharge summaries for patients who have received inpatient care 16 but its use in the outpatient setting for real-time data capture and development of clinic letters has received little attention and we have identified only a single report from a cancer clinic. 17 As far as we are aware, the potential benefits of such a document in a cardiac outpatient setting have not been examined.…”
Section: Introductionmentioning
confidence: 99%